Immunocytochemical markers in acute leukaemias diagnosis - Gluzman, D.F.; Nadgornaya, V.A.; Sklyarenko, L.M.; Ivanovskaya, T.S.; Poludnenko, L.Yu.; Ukrainskaya, N.I. (Experimental Oncology, 2010)
The study included 1742 patients with acute myeloblastic leukaemias (AML) and acute lymphoblastic leukaemias (ALL), Kyiv city residents and patients from 20 regions of Ukraine. Bone marrow and blood smears were sent at diagnosis to Reference Center. The analysis was based on May-Grünvald-Giemza (MGG) stain and cytochemical reactions (MPO, acNSE, CAE, AP, PAS). Immunocytochemical techniques (APAAP, LSAB) and broad panel of monoclonal antibodies (MoAbs) against lineage specific and differentiation antigens of leukocytes were employed for immunophenotyping of leukemic blast cells directly in blood and bone marrow smears. Different types of AML were defined by the expression of the cell surface and cytoplasmic antigens. Immunocytochemical study was required especially in diagnosing of AML with minimal differentiation, acute megakaryoblastic leukaemia, acute erythroid leukaemia and acute leukaemias of ambiguous lineage. Acute lymphoblastic leukaemias was broadly classified into B-lineage and T-lineage ALL. According to the degree of B-lymphoid differentiation of the blast cells four subtypes of B-lineage ALL were established. T-lineage ALL observed in patients were also divided into four subtypes. Immunocytochemical examination was required to diagnose AL of ambiguous lineage with no clear evidence of lineage differentiation (acute undifferentiated leukaemia) or those with blasts that express markers of more than one lineage (mixed phenotype acute leukaemias).